2004
DOI: 10.1021/jp022478q
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg Series as Ionization Channels:  Photoabsorption and Photoionization of the Atmospherically Relevant Molecule NO

Abstract: The photoionization of nitric oxide from its ground state has been studied with the molecular-adapted quantum defect orbital (MQDO) method. Partial differential oscillator strengths for the different Rydberg series that constitute the ionization channels of NO from its ground state have been calculated up to a photon energy of 60 eV. The continuity of the calculated differential oscillator strengths across the ionization threshold, that is, in the discrete and continuous regions of the spectrum, has been adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We have recently reported several studies of the vibronic and continuous transitions of NO 21,22,29 which indicated that the outermost molecular orbital of the ground state, 2π, resembles closely a "united atom" 3dπ orbital of reduced size with a smaller 2pπ contribution, because of the asymmetry of the molecule. 30 The presently calculated nonperturbed electronic transition moments are collected in Table 3 along with those reported by Galluser and Dressler.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported several studies of the vibronic and continuous transitions of NO 21,22,29 which indicated that the outermost molecular orbital of the ground state, 2π, resembles closely a "united atom" 3dπ orbital of reduced size with a smaller 2pπ contribution, because of the asymmetry of the molecule. 30 The presently calculated nonperturbed electronic transition moments are collected in Table 3 along with those reported by Galluser and Dressler.…”
Section: Results and Analysismentioning
confidence: 99%
“…We have recently reported several studies of the vibronic and continuous transitions of NO ,, which indicated that the outermost molecular orbital of the ground state, 2π, resembles closely a “united atom” 3dπ orbital of reduced size with a smaller 2pπ contribution, because of the asymmetry of the molecule …”
Section: Results and Analysismentioning
confidence: 99%
“…The photoabsorption processes experienced in the ionosphere by CF 2 Cl 2 and CF 3 Cl have been calculated and analyzed with the molecular quantum defect orbital (MQDO) approach. This methodology has, in previous applications to a variety of molecules, proved to yield correct intensities for bound Rydberg transitions 8–13, as well as for photoionization cross sections 14–17.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has proved to be reliable in photoionization studies on radicals such as NO, CH, NH 4 , and H 3 O. [23][24][25] Here, we have calculated photoionization cross section for the production of the CH 3 + and SiH 3 + ions in their lower electronic states with the MQDO method. In addition, we have analyzed the contribution of the different Rydberg series that constitute the ionization channels from the outermost orbitals for both radicals.…”
Section: Introductionmentioning
confidence: 99%